2016
DOI: 10.4143/crt.2015.088
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measurement of Cosmetic Outcomes of Breast Conserving Therapy Using BCCT.core

Abstract: PurposeThe purpose of this study is to evaluate objective cosmetic outcomes and factors related to breast-conserving therapy (BCT) using the BCCT.core software.Materials and MethodsFifty-one patients who received BCT with informed consent were evaluated using the BCCT.core software. Patients were divided into two groups based on the BCCT score: excellent or good (n=42) vs. fair or poor (n=9). Analysis of clinical factors was performed to determine factors affecting cosmetic outcomes.ResultsThe objective cosmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 20 publications
2
28
0
4
Order By: Relevance
“…Cardoso et al [ 18 ] reported that the BCCT-core program was an objective evaluation tool for the evaluation of breast cosmesis. Yu et al [ 19 ] also reported the validity of the BCCT-core program in assessing the outcomes in patients undergoing breast conserving surgery and adjuvant radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Cardoso et al [ 18 ] reported that the BCCT-core program was an objective evaluation tool for the evaluation of breast cosmesis. Yu et al [ 19 ] also reported the validity of the BCCT-core program in assessing the outcomes in patients undergoing breast conserving surgery and adjuvant radiation.…”
Section: Discussionmentioning
confidence: 99%
“…En varias publicaciones se contrastan los métodos ya existentes con estimaciones subjetivas de simetría, normalmente empleando la escala de Harris por parte de paneles de expertos. (27)(28)(29) . Fitzal y Krois (9,22) validan la última versión de su sistema de dos formas diferentes: por un lado, evalúan las impresiones de un solo observador en una muestra de 50 pacientes frente a la puntuación de su aplicación informática.…”
Section: Figura 9 Diagramas De Cajas Y Bigotes Que Muestran Las Difeunclassified
“…Ocurre lo contrario con los parámetros frente a los que hemos comparado GBAI: la literatura los aplica solamente a casos con cirugía tras cáncer de mama. (29) Nuestro estudio es el primero en evaluar objetivamente la asimetría mamaria en pacientes de Cirugía Estética con BSI, BCCT y OBCSN.…”
Section: Figura 9 Diagramas De Cajas Y Bigotes Que Muestran Las Difeunclassified
See 1 more Smart Citation
“…Dalam proses penilaian hasil dari BCT dari segi bedah kosmetik, ada beberapa hal penting yang harus menjadi pertimbangan [10][11][12][13][14][15]…”
Section: Diskusiunclassified